Retrospective study of fire setting among boys in a child welfare sample - Brereton, Alexandra L. (Youth violence and juvenile justice, 2020)
This study aimed to assess fire-setting behaviors within a child welfare sample. The youth were divided into four groups based on their fire-setting behavior (e.g., no incidents, one incident, multiple minor incidents, and multiple severe incidents). Groups were compared based on five factors: overt antisocial behavior, covert antisocial behavior, global adjustment, psychiatric history, and learning deficits. Fire setters displayed more delinquent behavior and had more extensive psychiatric histories than non-fire- setting youth. Further, the youth with multiple serious incidents of fire-setting behavior displayed more delinquent behavior and had more extensive psychiatric histories than any of the fire-setting groups. These findings clearly suggest that fire setters, as a group, are not homogeneous with respect to antisocial behavior or psychiatric impairment and that gravity of fire setting increased as a function of greater psychopathology and greater delinquency when compared to their peers.